Positive behavioural support for children and adolescents with learning disabilities and behaviour that challenges: an initial exploration of service use and costs. Issue 4 (3rd October 2016) - Iemmi, Valentina; Knapp, Martin; Reid, Caroline; Sholl, Catherine; Ferdinand, Monique; Buescher, Ariane; Trachtenberg, Marija
Abstract : Purpose: Positive behavioural support has been considered as a valuable alternative to residential care for children and adolescents with learning disabilities and behaviour that challenges. While recent evidence suggests it has a positive impact on behaviour and carer ability to cope, there is little evidence of its economic costs or benefits. The paper aims to discuss this issue. Design/methodology/approach: An exploratory cross-sectional study was conducted to evaluate the cost of providing positive behavioural support to ten children and adolescents with learning disabilities and behaviour that challenges living in the community in Ealing, West London. Comparison was also made with the cost estimate of possible alternative support packages for children and adolescents with learning disabilities and behaviour that challenges in the UK, as obtained through a Delphi exercise. Findings: Total cost of services per child was £1, 454 per week for young people supported short-term, and £1, 402 supported long-term. Children and adolescents were making use of a range of social care, education and health services. Over the full sample, half of the total cost was accounted for by education services. The Delphi exercise estimated the weekly cost of residential-based care as more expensive than the cost of community-based care for children and adolescents with learning disabilities and behaviour that challenges. At the end of the ITSBS, all ten children and adolescents initially at risk of imminent residential placement were living in the community with less service-intensive and less expensive support. This suggests that avoiding residential-based care could reduce costs in the long term. Originality/value: Positive behavioural support has potential to support people with learning disabilities and behaviour that challenges in the community, leading to potential cost advantages. However, this is a small study and more robust research is needed.